2011
DOI: 10.1890/10-2442.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and the evolutionary divergence of plant parasites

Abstract: The coexistence of closely related plant parasites is widespread. Yet, understanding the ecological determinants of evolutionary divergence in plant parasites remains an issue. Niche differentiation through resource specialization has been widely researched, but it hardly explains the coexistence of parasites exploiting the same host plant. Time-partitioning has so far received less attention, although in temperate climates, parasites may specialize on either the early or the late season. Accordingly, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…Further experimental investigations taking into account the pathogenic and saprophytic phases of the disease cycle (40,41), guided by theory (43,47), would be appropriate for characterizing the effect of seasonality on year-to-year disease transmission. Indeed, seasonality plays a role in short-term pathogen evolution by causing alternating periods of high transmission and population bottlenecks (8).…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental investigations taking into account the pathogenic and saprophytic phases of the disease cycle (40,41), guided by theory (43,47), would be appropriate for characterizing the effect of seasonality on year-to-year disease transmission. Indeed, seasonality plays a role in short-term pathogen evolution by causing alternating periods of high transmission and population bottlenecks (8).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in more diverse grassland communities, we also observed infected plant species to be less likely to be infected by multiple pathogens (Table 2b, Appendix F). Co-infection of pathogens is equally governed by initial host encounter and non-host shielding that limits pathogen spread, which also increases competition between pathogens for shared host tissue (Finckh et al 2000, Barrett et al 2009, Hamelin et al 2011.…”
Section: Effects Of Plant Species Diversity On Pathogen Group Diversimentioning
confidence: 99%
“…Models on plant parasites, for instance, have indicated that evolutionary divergence of parasite phenotypes can be driven by seasonal transmission and associated fitness trade-offs (Hamelin et al, 2011), such as may also occur with annual treatments and reduced density-dependent factors. One such recent model describes how competition explains intra-host diversification of parasites (Rascalou and Gourbiere, 2014).…”
Section: Elucidating the Potential Role Of Hybridisation And Introgrementioning
confidence: 99%